2013
DOI: 10.1042/bj20130540
|View full text |Cite
|
Sign up to set email alerts
|

Mining the bacterial unknown proteome: identification and characterization of a novel family of highly conserved protective antigens in Staphylococcus aureus

Abstract: In the human pathogen Staphylococcus aureus, there exists an enormous diversity of proteins containing DUFs (domains of unknown function). In the present study, we characterized the family of conserved staphylococcal antigens (Csa) classified as DUF576 and taxonomically restricted to Staphylococci. The 18 Csa paralogues in S. aureus Newman are highly similar at the sequence level, yet were found to be expressed in multiple cellular locations. Extracellular Csa1A was shown to be post-translationally processed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 55 publications
0
32
0
4
Order By: Relevance
“…Csa1A is highly conserved across different S. aureus isolates (Fig. 1A) and belongs to a family of proteins encoded in at least four distinct loci sharing from 54% to 91% sequence identity (7). The other three selected antigens are secreted virulence factors and include α-hemolysin (Hla), ess extracellular A (EsxA), and ess extracellular B (EsxB).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Csa1A is highly conserved across different S. aureus isolates (Fig. 1A) and belongs to a family of proteins encoded in at least four distinct loci sharing from 54% to 91% sequence identity (7). The other three selected antigens are secreted virulence factors and include α-hemolysin (Hla), ess extracellular A (EsxA), and ess extracellular B (EsxB).…”
Section: Resultsmentioning
confidence: 99%
“…The antigens included in our candidate combination vaccine were selected among surface and secreted factors previously shown to be protective and involved in S. aureus virulence. Two of them, the ferric hydroxamate-binding lipoprotein FhuD2 and the putative lipoprotein named conserved staphylococcal antigen 1A (Csa1A), are surface-exposed antigens that were identified in our laboratories using MS-based surfome analyses and bioinformatics (6,7). FhuD2 is a lipoprotein involved in iron uptake and in early stages of invasive S. aureus infection (6,8,9).…”
Section: Resultsmentioning
confidence: 99%
“…Csa1A belongs to a family of 10 to 20 conserved staphylococcal antigens (Csa) classified as DUF576 and taxonomically restricted to staphylococci. The structures of the Lpp Csa1A and Csa1B were determined, and it has been shown that they conferred protective immunity against S. aureus in animal models (128).…”
Section: Lpp As Vaccine Candidatesmentioning
confidence: 99%
“…Both Tlpp1 and Tlpp3 possessed signal peptides and “lipobox” sequences, whereas Tlpp2 comprised a transmembrane helix domain at the N-terminal (S1A Fig). These proteins were annotated as Tlpps belonging to a domain of unknown function (DUF) 576 protein family on the Pfam database [22]. Considering that Tlpps account for more than 62.6% of amino acid identity (S1B Fig), we prepared recombinant Tlpp1 proteins (Fig 1C) and the corresponding antibodies, and verified the authority of the β-lactam-stimulated proteins through Western blot analysis (Fig 1D).…”
Section: Resultsmentioning
confidence: 99%